Reindeer Herding and History in the Mountains of Southern Sápmi - Wennstedt Edvinger, Britta (Current Swedish Archaeology, 2002)
During the summers of 1998-2000 four Saami villages in southern Sapmi carried out a survey of traditional reindeer herding sites. Reindeer herding of today engages a small Saami minority, but the reindeer herders are important as bearers of Saami culture and language. Reindeer herding has, however, been called into question from several different directions. In this process, which often leads to court, the ability of the Saami villages to present evidence of previous reindeer herding in a region, either in written records or as remains in the landscape, has become an argument for the continued rights of use of certain winter-grazing areas. As a result, archaeology has acquired a new relevance for the Saami villages. But the procedures of archaeological surveys and of the cultural heritage conservation in Sweden are based on ethnocentric assumptions. In a cultural sense, Sapmi of the past and present-day Sweden belong to two different continents, even though they happen to be situated in the same comer of the world. When working with Saami history it is necessary to do away with the distinction between "nature" and "culture", just like a number of other dualisms that are relevant only in a (modern) Western context. If we replace "nature" and "culture" with "environment", we will increase our possibilities to translate Saami history into the language of archaeology and to make archaeology relevant to local people in the mountain region.